“Trocadilho”: uma proposta pedagógica circense para a Educação Infantil (Revista NUPEART, 2021)
This article presents one of the results of a master's research developed in collaboration with children from the Pre-School II class and teachers at a CREI (Reference Center for Early Childhood Education) on the outskirts of João Pessoa-PB. From the professional artistic experience acquired at the Circus, the path of the creation of a pedagogical proposal based on the junction between circus art, games and children's plays is narrated. Such proposal, called “Trocadilho”, is analyzed when describing principles and contents proper to the circus artistic and educational knowledge and identifying parameters that guide the curriculum practiced based on the BNCC guidelines. The intervention in the educational environment, provoked by the proposal, allows us to affirm that it is possible to learn the circus through children's cultures, while allowing the school community and, not just the children, to play through the circus.